The Meaning of War in the Qur’an: Perspectives from Tafsir al-Munir and Tafsir at-Thabari - Muhammad Adib Akrom; Dian Erwanto; Muhammad Athaillah (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This research examines the war verses through a comparative study between the tafsir al-Munir by Wahbah az-Zuhaili and the tafsir Jami' Al Bayan fi Tafsir al-Qur'an by at-Thabari. War is a theme in the Koran that is often misinterpreted to legitimize violence and terrorism. Therefore, it is important to understand war verses in the correct context. This research uses qualitative methods with descriptive analysis which aims to identify, classify and interpret war verses from these two interpretations. The results of the analysis carried out show that there are differences in interpretation which tend to be more textual and literal and those which are more contextual and holistic. In this research, first, discussing the differences between Qital, Jihad, and Harb, where these three lafadh are often used in contexts related to war, second, differences in interpretation regarding the study of war verses between Wahbah Az-Zuhaili and Ibnu Jarir At-Thabari, second, highlighting the relevance of war verses in a modern context, which are expected to enrich Islamic knowledge and help correct wrong understandings about jihad.